Microscopic identification and PCR based assay in feed analysis - G. Savoini (Italian Journal of Animal Science, 2011)
which 20% is manufactured compound feed (Brookes, 2001). This production level imposes an adequate high quality standards especially with regard to the EU Commission’s ban on the use of processed animal proteins. From this point of view a complete separation of plants dedicated to feed production from plants processing raw material, stretcher rules for traceability of animal by-products, as well as feed analysis and feed inspection of raw material or compound feed, are all critical points in food safety. In a previous study (Pinotti et al., 2002) it was suggested that higher protein level in compound feed could be a risk factor for low level cross contamination with meat and bone meal. This could be associated with the same route followed by protein sources, in the feed processing/manufacturing (collection, transport, milling, etc)...........